The Effect of Professional Development on Employee Performance Moderated by Career Level at PT. Samsung Elektronik Indonesia North Sumatra Region 02 Medan - Nidal, Yasser; Putra, Rizki; Ardiani, Winda (Formosa Journal of Applied Sciences, 2024)
This study aims to determine the effect of professional development on employee performance moderated by career paths at PT Samsung Elektronik Indonesia North Sumatra 02 Medan. This type of research is associative research using quantitative methods. The sample in this study was 120 respondents who were measured by purposive sampling method. The data obtained were analyzed using statistical formulas, namely by using moderated regression analysis (MRA) analysis whose processing was carried out with the Smart PLS version 3.0 program. The results of this study indicate that professional development has a positive and significant effect on employee performance as evidenced by the tcount value of 10.284> t table 1.98 with a significance of 0.00 <0.05. Career level is significantly able to moderate the effect of professional development on employee performance as evidenced by the significance value of 0.00 <0.05.